Selling Terroir: A Geographical Analysis of the South-Central Wisconsin Wine Market - Schara, Colton; Peters, Elizabeth; Koser, Jonathan; Goodell, Jonathan (My University, 2014)
With increasing sales, an expanding number of wineries, and a growing consumer base, wine in Wisconsin is growing in popularity and importance. In an effort to better understand this burgeoning industry, this research aims to apply the concept of terroir to Wisconsin wines. An exploration of terroir through its history, cultural significance, use in marketing, and its effect on the wine industry provides a five part framework for the term: physical, commercial, traditional, historical, and cultural. Using this robust and holistic definition of terroir, it then examines the marketable terroir and perceived image of Wisconsin wines though landscape observation, surveys, wine label analysis, and website analysis based around South-Central Wisconsin. It is clear that there is a general lack of terroir understanding as well as discrimination against Wisconsin wines based off of preconceived reputation, climate, price, and competition from other more well-known locales. There is also a notable lack of place emphasis in the marketing of wine, especially when it comes to physical geographic characteristics. The wine market will survive in Wisconsin but in order for it to sustain growth, it is recommended that wine producers in the state begin to use place-based marketing and the elements of terroir to craft an identity for themselves. This is a process which takes a lot of time but will likely pay off in the end.
Includes Photographs, Figures, Charts, Illustrations, Appendices, Air Photos and Bibliography.
Keywords: Terroir; Wineries; Marketing; South-Central Wisconsin; Wine